Pengaruh Frekuensi Menguras Terhadap Jumlah Candida sp. Pada Air Bak Toilet Wanita di SPBU Surakarta - Taufiq Qurrohman, Muhammad; Wahyu Nugroho, Rosit (Jurusan Biologi UIN Alauddin Makassar, 2015)
Candida sp. are dimorphic fungi that grow as the yeast cells. These fungi are commonly found on stagnant water, for example is toilet water tub. Several factors that affect the growth of Candida sp. on the toilet water tub are the source of water, toilet users, and the draining. The purpose of this research is to find out the effect of draining frequency on the number of Candida sp. in womenâs toilet water tub at the gas station in Surakarta. This study is an observational analytical research with cross sectional approach. The examination was showed that the average number of Candida sp. in the regularly drained toilet water tubs was 66,67 colonies/10ml sample and the average number ofCandida sp. in the irregularly drained toilet water tubs was 240,3 colonies/10ml sample. The datawere tested by using independent t-tes and the significant number was 0,003 (P < 0,05). It could beconcluded that there was a distinctive effect of draining frequency on the number of Candida sp. inwomenâs toilet water tub at the gas station in Surakarta.Keywords: Candida sp., draining, water tub